2009
DOI: 10.1051/forest/2009052
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of isolated Picea balfouriana populations from the southeast of the Qinghai-Tibet Plateau

Abstract: Abstract• The objective of this work is to estimate the level of genetic variation and pattern of genetic structure of isolated Picea balfouriana populations.• Nine SSR markers and six STS markers were assayed in ten natural populations of P. balfouriana, which is a regionally distributed conifer species in the southeast of the Qinghai-Tibet Plateau.• Expected heterozygosity ranged from 0.592 to 0.710 based on SSRs, and from 0.489 to 0.635 based on STS markers. The SSR and STS markers revealed that 11% and 12%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Habitat fragmentation is expected to have a detrimental impact on the genetic diversity of plant species (O'Connell et al 2006;Isagi et al 2007;Lu et al 2009), but several studies have revealed that population responses to fragmentation are variable (Jump and Penuelas 2006;Kettle et al 2007). In this study, the genetic diversity (H Sne = 0.144) based on ISSR markers was within the general range previously detected for ssp.…”
Section: Discussionsupporting
confidence: 79%
“…Habitat fragmentation is expected to have a detrimental impact on the genetic diversity of plant species (O'Connell et al 2006;Isagi et al 2007;Lu et al 2009), but several studies have revealed that population responses to fragmentation are variable (Jump and Penuelas 2006;Kettle et al 2007). In this study, the genetic diversity (H Sne = 0.144) based on ISSR markers was within the general range previously detected for ssp.…”
Section: Discussionsupporting
confidence: 79%
“…It can also slow down the extinction process caused by adaptation and evolution [ 38 ]. Microsatellite markers are efficient in examining genetic diversity and exploring genetic relationships in plants, and have been widely used to investigate the genetic diversity of Qinghai-Tibetan Plateau species [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite, also known as simple sequence repeat (SSR), is widely used in many molecular genetic applications including genotype mapping (ACHERÉ et al, 2004;ECHT et al, 2011;KANG et al, 2010), population structure and genetic diversity analysis (ESPINOZA et al, 2012;PLUESS et al, 2013;LU et al, 2009), and gene flow and germplasm conservation studies (SHIMONO et al, 2011). SSR markers are co-dominant, abundant and evenly distributed in genomes of plants, multi-allelic, highly polymorphic and are easily detectable by simple polymerase chain reaction (PCR) technology (HODGETTS et al, 2001;RAJORA et al, 2001;PEAKALL et al, 1998).…”
Section: Introductionmentioning
confidence: 99%